The Principle of Exhausting the Court’s Jurisdiction and its Effect on Reconsidering the Judgment Issued in the Subject Matter of the Lawsuit according to the Law of Civil Procedure Issued by Royal Decree No. (M/1) Dated 22/1/1435 AH - Abdelkawy, Huda (Journal of Legal Sciences, 2025)
The principle of exhaustion of jurisdiction is one of the important principles in judicial organization. The regulatory texts in the system of Sharia litigation refer to its adoption and implementation. Some scattered texts in the system indicate that as soon as a judicial ruling is issued on the subject of the dispute, the jurisdiction of the judge ends. For example, Article (167) of the system states, "If the jurisdiction of the judge ends regarding a case before the ruling is pronounced." This article indicates that the jurisdiction of the judge ends immediately upon issuing the judicial ruling in the case, and the end of the judge’s jurisdiction is referred to as the exhaustion of jurisdiction for the judge or the court. As a result of this principle, the judge is not allowed to reconsider the case or the judicial ruling issued therein, although the texts of the system do not explicitly mention this. Moreover, there are texts that contradict this principle, such as Article (189) of the system, which allows the judge to reconsider the ruling issued for modification. This text contradicts the principle of exhaustion of jurisdiction. This prompted a discussion of the topic, addressing the concept of the exhaustion of the judge’s jurisdiction, its importance, and the exceptions that apply to it, followed by the conclusion of the research, which included the findings and recommendations.